Estrutura e composição da ictiofauna de riachos do rio Paranapanema, Sudeste e Sul do Brasil - Castro, Ricardo M. C. (2003)
Seventeen 100 m long streams stretches, none of an order higher than three, were sampled to both sides of the main channel of Rio Paranapanema in the States of São Paulo and Paraná, southeastern and southern Brazil. Each stream stretch had its midpoint located with a GPS satellite receiver and had its fish fauna sampled via a standardized environmental data and fish collection methodology (primarily utilizing electrofishing) with the aim of providing the following information about each stream: 1) the taxonomic composition of the fish fauna and the contribution of each species in that stream in terms of both number of individuals and biomass; 2) a photographic documentation of the live coloration of representative speci-mens of each collected species; and 3) the description of each sampled environment, with colored photographic illustra-tions and details of the main biotic and abiotic parameters. Overall 3,683 fishes were collected, belonging to six orders, 16 families, 37 genera, and 52 species, with a total biomass of 16.8 kg. Of the collected species, approximately 36% were Siluriformes, 36% Characiformes, 11% Gymnotiformes, 10% Perciformes, 4% Cyprinodontiformes, and 2% Synbranchiformes. The most abundant species in terms of total number of individuals were Astyanax altiparanae (15.2%) and Astyanax sp. 1 (12.3%); The species with the largest biomasses were Astyanax altiparanae (28%) and Geophagus brasiliensis (13%). In terms of abundance and biomass collected for each family, the Characidae was clearly the predominant family followed by the Loricariidae, Pimelodidae, and Cichlidae. Among the sampled stream stretches, locality 14 with 24 species and locality 13 with five species yielded the highest and lowest richness in terms of species numbers, respectively. This coincides with the values obtained for the Shannon-Wienner index of specific diversity (H´ = 0.99 and 0.32, respectively). The median species richness for all streams stretches was 11. In the species richness estimate by extrapolation for all 17 sampled stream stretches, a value of 69 species was obtained (with a standard error of four) indicating the need for an additional moderate sampling effort to reach the asymptote of the curve. Of the 52 collected species, eight (approximately 15% of the total) are clearly new to science and five other species (approximately 10% of the total) are of indefinite taxonomic status and require further analysis. Three of the captured species are introduced (approximately 6% of the total). Analysis of the trophic and spatial structure of the studied fish fauna indicates that the 10 numerically dominant species in the sampled streams can be grouped into four guilds that are in decreasing order of numeric importance: nektonic omnivores; benthonic invertivores; periphytovores; and benthonic omnivores. An identification key for all the species of fish collected during this study it is provided.